Acridone-based derivatives exhibit excellent third-order NLO properties by extending the π system. (7th May 2021) - Jia, Jianhong; Liang, Guanqiu; Zhu, Ziqiang; Wang, Jian; She, Yuanbin
Abstract: Acridone derivatives have much attracted attention due to their objective photoelectric properties. However, their applications in nonlinear optical (NLO) materials are rarely studied. In this work, we designed and synthesized four D-π-A-π-D acridone derivatives and one D-A-D type derivative as comparison. The effects of the structure on photophysics, electrochemistry and the third-order nonlinear optics were analyzed by UV spectrophotometer, fluorescence spectrophotometer, cyclic voltammetry and Z-scan technique. The results show that the introduction of acetylene group as a bridge is conducive to intramolecular charge transfer and can maintain the planarity of the molecule and enhances the third-order NLO properties. In the four target products, YA4 has the best third-order NLO properties, with its second-order hyperpolarizability γ (γ = 5.792 × 10 −33 esu) 1.36 times that of YA1 (γ = 4.262 × 10 −33 esu) and 6267 times that of urea ( γ  = 0.68 × 10 −36 esu). The study showed that introducing an appropriate length of alkane chain into acridone derivatives can effectively reduce the intermolecular interference and improve their third-order NLO performance. Graphical abstract: Image 1 Highlights: A series of acridone derivatives were synthesized. Introducing acetylene groups as π-bridge is beneficial to ICT and enhances the third-order NLO properties. The acridone derivatives containing strong electron-donating groups have a large NLO responses.